Are Emirati consumers in United Arab Emirates open to alternative proteins? Insights into their attitudes and willingness to replace animal protein sources - Sajid Maqsood; Feyisola Fisayo Ajayi; Hussein Mostafa; Kehinde Ganiyat Lawal; Juliet Mubaiwa; Noora Alantali; Maryam Alshihhi; Meera Aldhaheri (Frontiers in Sustainable Food Systems)
IntroductionReplacing animal protein with alternative sources is gaining popularity for sustainable food systems and reducing greenhouse gas emissions. Understanding consumers’ views on alternative proteins is crucial for widespread adoption. Research shows acceptance and preferences vary across cultures, but there is no data for the United Arab Emirates (UAE). This study investigates the influence of dietary habits, objective knowledge, attitudes, subjective norms, and perceived behavioral control on willingness to replace meat with alternatives by Emiratis. Further, the factors that drive willingness to replace meat are investigated.MethodsAn online survey with 1,666 native UAE nationals assessed their knowledge, attitudes, and acceptance of plant-based proteins, microalgae, edible insects, and cultured meat. In the study, Emirati citizens between the ages of 18 and 65, who have resided in the UAE for most of their lives, were selected. A total of 1,666 out of 2,600 individuals who expressed interest participated in the study. Data was analyzed using Pearson Chi-square to correlate two demographic variables and linear regression to identify predictors that influence the participants to shift toward alternative proteins.ResultsAbout 51.2% of Emiratis were familiar with alternative proteins, with 74% preferring plant-based options. Using linear regression model, the following were factors influencing willingness to replace meat: (i) meat, dairy and cereal attachment, (ii) sustainability awareness, (iii) awareness of alternative proteins, (iv) nutrition consciousness, (v) availability of alternative proteins, (vi) taste of alternative proteins products, and (vii) advertisement. Sustainability concerns alone did not drive purchases, but focusing on sensory qualities and advertising could lead to a shift.DiscussionOur findings bring insights on the knowledge, attitude, and determinants of willingness of native Emiratis toward the purchase and replacement of meat with “alternative proteins-based” food products. The successful shift to alternative proteins will depend on enhancing consumer sensory satisfaction, cost, doubts, health, and cultural significance. This study indicates that Emiratis consume animal proteins on a regular basis, leading us to classify them as individuals with a high meat intake. Incorporating plant-based proteins into food design shows promise for promoting sustainable diets in the UAE and beyond.